The Comparsion of the Effectiveness of Self-Acceptence Group Therapy By Draydan Method and NA Training on Addicts' Mental Health Components - Medi Zarebahramabadi; Mohammad ali Mohamadyfar; Nasroollah Erfani; Moustafa Mashayekhipour (Drug Control Headquarters, Research and Education Office, 2012)
Introduction: This research aimed at the effectiveness of self-acceptance group therapy by Dryden method in comparison with NA on the components of addicts' mental health. Method: The method of this Semi-experimental research was comparison between unmatched groups. The population consisted of addicted pepole who attended to rehabilitative addiction institutes in Hamedan city in 1389-90. In self-acceptance group section, 27 people were selected as voluntary sample and were affected on self-acceptance group therapy by Dryden method for ten sessions weekly. In NA group section also 37 people were selected as sample group voluntary and participated in weekly sessions for six month. General Health Questionnaire (28 items) was administered among selected sample. Results: The results showed that self-acceptance group therapy had positive effect on depression, anxiety and addicts' general health. Also, NA group had positive effect on physical symptoms, depression, anxiety and addicts' general health. Other results showed that the range of NA effect on addicted depression was more effective than self-acceptance group therapy. Conclusion: Participate in NA training and self-acceptance group therapy increase mental health in addicts.